Modified Application of Nitrogen Fertilizer for Increasing Rice Variety Tolerance toward Submergence Stress - Gribaldi Gribaldi; Nurlaili Nurlaili; Nurmala Dewi; Ekawati Danial; Firnawati Sakalena; Rujito A. Suwignyo (International Journal of Agronomy)
This research was conducted from July to October 2015, using Randomized Block Design with two treatment factors and three replications for each treatment. The first factor was rice varieties (V): V1 = IR 64; V2 = Inpara 5. The second factor was fertilizer (N): N0: without submergence, all N fertilizer was given during planting; N1: all N fertilizer dose was given during planting; and N2: 1/2 dose of N fertilizer was given during planting; the rest was given at 42 days after planting. The submergence was during 7–14 days after planting; N3 = the entire dose of N fertilizer that was given during planting, N4 = 1/2 the dose of N fertilizer that was given during planting, and the rest was given at 42 days after planting. The submergence was during 7–14 and 28–35 days after planting. The results showed that the management of nitrogen fertilizer application had effect on rice growth and production which experienced dirty water submergence stress; the application of 1/2 dose of N fertilizer given during planting had the best effect on rice growth and production; the longer the submergence period for rice variety, the higher the effect on rice growth and production.